2019
DOI: 10.15252/embr.201948336
|View full text |Cite
|
Sign up to set email alerts
|

The ion channel function of polycystin‐1 in the polycystin‐1/polycystin‐2 complex

Abstract: Autosomal dominant polycystic kidney disease (ADPKD) is caused by mutations in PKD1 or PKD2 gene, encoding the polycystic kidney disease protein polycystin‐1 and the transient receptor potential channel polycystin‐2 (also known as TRPP2), respectively. Polycystin‐1 and polycystin‐2 form a receptor–ion channel complex located in primary cilia. The function of this complex, especially the role of polycystin‐1, is largely unknown due to the lack of a reliable functional assay. In this study, we dissect the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 67 publications
(243 reference statements)
1
59
0
Order By: Relevance
“…The most common inherited cause of renal failure, ADPKD, is a systemic ciliopathy that presents with progressive renal cyst expansion and extrarenal manifestations following loss-J o u r n a l P r e -p r o o f of-function mutations in the genes PKD1 and PKD2 (Figure 3) 38 . The cognate renal ciliary proteins, polycystin 1 (PC1) and polycystin 2 (PC2), form heterodimeric receptor-ion channel complexes that localize to the primary cilia, prompting intensive study into their role as an underlying cause of common renal ciliopathies 39,40 . PC1 is a large G-protein coupled receptor (GPCR), of which the ligand/s and activating stimuli are still unknown 41 .…”
Section: Autosomal Dominant Polycystic Kidney Diseasementioning
confidence: 99%
“…The most common inherited cause of renal failure, ADPKD, is a systemic ciliopathy that presents with progressive renal cyst expansion and extrarenal manifestations following loss-J o u r n a l P r e -p r o o f of-function mutations in the genes PKD1 and PKD2 (Figure 3) 38 . The cognate renal ciliary proteins, polycystin 1 (PC1) and polycystin 2 (PC2), form heterodimeric receptor-ion channel complexes that localize to the primary cilia, prompting intensive study into their role as an underlying cause of common renal ciliopathies 39,40 . PC1 is a large G-protein coupled receptor (GPCR), of which the ligand/s and activating stimuli are still unknown 41 .…”
Section: Autosomal Dominant Polycystic Kidney Diseasementioning
confidence: 99%
“…The cystic epithelial and tubular cells produce renin, angiotensinogen and angiotensin II which are secreted into cystic fluid [27,28]. ADPKD, affecting one in 400-1000 individuals, is caused by mutations in two genes, PKD1 or PKD2 [29]. Most ADPKD cases (85%) are associated with mutations of PKD1 gene (located at 16p13.3 chromosome).…”
Section: Polycystic Kidney Diseasementioning
confidence: 99%
“…The Ca 2+ influx is induced by binding of Wnt ligands to the extracellular PC1 domain in the presence of PC2. Although it is known that PKD1 or PKD2 mutations disrupt complex formation, reducing channel permeability [42], the exact molecular mechanisms that contribute to the development of ADPKD are poorly understood [29]. Furthermore, recent studies suggested that the pathogenic mechanism of PKD could be independent of ion-channel activity of PC1, which may be irrelevant to the ion currents in the cilium, while PC2 may act as a monovalent cation-selective channel [43].…”
Section: Polycystic Kidney Diseasementioning
confidence: 99%
“…Indeed, cryogenic electron microscopy (cryo-EM) structures have captured polycystin-2 in its homomeric form and in complex with polycystin-1 (14)(15)(16)(17). Recent work expressing PKD1 with PKD2 genes demonstrates that ion selectivity can be altered when polycystin-1 is incorporated, but this only occurs when polycystin-2 is trapped in an open state by mutations in pore residues (18). Thus, these results do not discern if polycystin-1 is operating as a chaperone for polycystin-2 or forms a bona fide ion channel with undetermined gating properties.…”
mentioning
confidence: 99%